Open Femoral Shaft Fractures in a Developing Country: Pattern of Presentation and Outcome of Treatment - Ekwedigwe, Henry Chinedum; Katchy, Amechi Uchenna; Ezeh, Richard Chukwunonye; Anieze, John Kene (Nigerian Journal of Orthopaedics and Trauma, 2019)
Background: The femur is one of the principal load‑bearing bones of the lower extremity. Femur fractures are among the most common fractures encountered in orthopaedic practice. Open femur fractures are always as a result of high‑velocity injury and almost invariably associated except for isolated gunshot injuries with multiple traumas. The aim of the study is to determine the pattern of presentation of open femur shaft fractures, associated injuries and outcome of treatment. Patients and Methodology: A 10‑year retrospective study done at National Orthopaedic Hospital, Enugu, from 2007 to 2016. Patients’ folders were retrieved from the Medical Records Department; patients’ biodata, cause of the injury and other relevant information were collated from the folders and their management followed up for 1 year. Data analysis was done with Statistical Product and Services Solution Version 22. Results: A total of 62 cases were reviewed. Treatment outcome of 50 patients that completed their management was analysed. The age range with the highest frequency was 21–30 years. Associated injuries were recorded in 77.4% of the patients. Thoresen’s combined excellent and good outcome was observed in 63.3% of the patients at a minimum of 1‑year follow‑up. Conclusion: Open femoral shaft fractures are more common in the younger age groups and usually associated with high frequency of associated injuries. The outcome of treatment of these fractures in our environment is good despite the limited resources usually encountered in a developing nation like ours.